Preparation method and application of composite nano-silver paper with low thermal expansion coefficient
By mixing nano -class ceramic materials with silver nano -navile mother liquids for separation, drying and pre -pressure treatment of solid fluid, composite nano -silver paper with a low heat expansion coefficient is prepared, and the existing nano -silver paper is hot in the packaging of the power electronic power module packaging. The problem of fatigue has significantly improved the hot and cold shock performance of the device and the stability of service.
Patent Information
- Application Number
- CN202411876544.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-01-21
AI Technical Summary
In the packaging of power electronic power modules, existing nano silver paper has a high thermal expansion coefficient, which has the potential for thermal fatigue cracking under hot and cold impact, which affects the service reliability of the device.
By mixing nano -grade ceramic materials with silver nano -noodles, it is separated, dry, and prestressed, and composite nano -silver paper with a low heat expansion coefficient is prepared. This method is added by the addition of nano -grade ceramic materials to reduce the thermal expansion coefficient of the sintering body after the thermal pressure, and improve the hot and cold impact performance.
The thermal expansion coefficient of the composite nano-silver paper is reduced, the elastic modulus is increased, and the interface bonding strength is enhanced, which significantly improves the service stability of the device under hot and cold shock.
Smart Images

Figure CN119332533A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of power electronic power module packaging, and in particular to a preparation method and application of composite nano silver paper with a low thermal expansion coefficient. Background Art
[0002] Power electronic power modules (IGBT modules, rectifier modules, etc.) are mainly used in flexible voltage DC transmission, rail transit, new energy vehicles, phased array radar and other fields that require efficient energy conversion, power amplification and voltage control. The high-frequency and high-voltage service working environment generates a lot of heat, and thermal fatigue problems seriously affect the service reliability of power modules.
[0003] Chinese patent application number CN118143263A discloses a nano silver paper and its preparation method and application. The preparation method includes diluting the silver nanowire mother liquor to obtain a silver nanowire dispersion, and then separating the solid and liquid to a paste under a negative pressure of 0.05MPa to 0.2MPa, and then separating the solid and liquid to a paste under a positive pressure of 0.1MPa to 1MPa until no liquid drips out to obtain a wet nano silver paper. After rinsing, vacuum drying, and low-temperature hot pressing, the nano silver paper is obtained. The nano silver paper obtained by this technical solution has properties similar to paper as a new thermal interface material, has a certain strength that can be mechanically cut, and has a simple preparation process, high production efficiency, strong batch stability, can be mass-produced, high yield, uniform and controllable film thickness and surface density, can realize low-temperature packaging interconnection, and the sintered interface layer after hot pressing sintering has the characteristics of high thermal conductivity, high electrical conductivity, low porosity, high service reliability, etc. However, the applicant found that when the nano silver paper is used for power electronic power module device packaging, because the thermal expansion coefficient of the copper-clad ceramic plate and chip in the power module is generally less than 5×10 -6 K -1 (50~200℃), while the thermal expansion coefficient of the copper plate or heat sink is about 17×10 -6 K -1 ~18×10 -6 K -1 (50~200℃), the difference between the two is large. Although nano silver paper as an interface material can effectively relieve the thermal stress between the two and improve the thermal fatigue performance after interconnection, the interface thermal expansion coefficient of nano silver paper after hot pressing packaging is about 18×10 -6 K -1 ~19×10 -6 K -1 (50~200℃), there is still a risk of thermal fatigue cracking during the temperature shock process of -65~150℃. Therefore, it is necessary to further improve the thermal shock performance of nano silver paper. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for preparing composite nano silver paper with a low thermal expansion coefficient and improved thermal shock performance.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing composite nano silver paper with low thermal expansion coefficient comprises the following steps: S1, diluting the dispersed solution of the surface-modified nano-ceramic material to obtain a diluted solution; S2, mixing the diluent and the silver nanowire mother liquor evenly to obtain a mixed liquor, wherein the solid content ratio of the nano-scale ceramic material in the diluent to the silver nanowire in the silver nanowire mother liquor is 0.3-5:100; S3, subjecting the mixed liquid to solid-liquid separation, drying, and pre-pressing to obtain composite nano silver paper.
[0006] In step S1, the surface modification includes the following steps: mixing a diluent, a dispersant, a surfactant, and a nano-ceramic material, and dispersing them evenly in a water bath environment at 40 to 80° C. to obtain a dispersed solution.
[0007] In the surface modification step, the mass percentage of diluent: dispersant: surfactant: nano-grade ceramic material is 100-5000: 0.01-0.5: 0.005-0.2:1.
[0008] The nano-scale ceramic material is one or more of SiC, AlN, diamond, Si3N4, Al2O3, and the particle size is 10 to 100 nm.
[0009] As a further improvement to the above technical solution: Contains at least one of the following features A to C; A. The diluent is one or more of ethylene glycol, glycerol, n-butanol, methyl amyl alcohol, acetic acid, caproic acid, and deionized water; B. The dispersant is one or more of polyvinyl pyrrolidone, polyvinyl butyral, polyethylene glycol, polyacrylamide, polyvinyl alcohol, and polyacrylic acid; C. The surfactant is one or more of silane coupling agent, sodium lauryl sulfate, sucrose fatty acid ester, alkyl glucoside, titanate, tetramethylammonium hydroxide, ethyl carbamate, hexadecyltrimethylammonium bromide, and ethylenediaminetetraacetic acid.
[0010] The dilution step is: adding the dispersed solution into deionized water and stirring evenly at a temperature of 25-80° C. to obtain a diluted solution.
[0011] In step S3, the pre-pressing temperature is 120-150° C., the pressure is 3-5 MPa, and the time is 1-5 min.
[0012] In step S3, the temperature during the drying is 35-80°C; when the drying is vacuum drying, the drying time is 5-10 minutes; when the drying is forced air drying, the drying time is 4-6 hours.
[0013] In step S1, the dispersion in the surface modification step is ultrasonic dispersion, and the dispersion time is 10 to 30 minutes.
[0014] In step S1, the stirring during dilution is mechanical stirring, with a rotation speed of 100 to 300 rpm and a time of 5 to 30 minutes.
[0015] In step S2, the diameter of the silver nanowires in the silver nanowire mother solution is 10-200 nm, and the length of the wire is 3-50 μm.
[0016] In step S3, solid-liquid separation is performed using external force, which is one or both of positive pressure and negative pressure.
[0017] The thickness of the composite nanosilver paper after low-temperature pre-pressing is 30-400 μm, and the surface density is 0.06-1.2 kg / m 2 , thickness and density fluctuations <5%, impurity content such as organic matter <1.5%.
[0018] An application of the composite nano silver paper prepared by the aforementioned preparation method in the packaging of power electronic power devices.
[0019] The application includes packaging interconnection between a chip and a substrate, or packaging interconnection between a substrate and a heat sink, wherein the packaging is hot pressing packaging with a temperature of 180 to 250° C., a pressure of 8 to 20 MPa, and a time of 3 to 10 minutes.
[0020] In the application, the chip is a square chip with a length ≥10mm and a width ≥10mm or a circular chip with a diameter ≥10mm, and the chip includes a Si-based chip, a GaAs chip, a SiC chip, an AlN chip, a Si3N4 chip, an Al2O3 chip, etc. The substrate is a substrate with a length ≥30mm or a width ≥30mm, and the substrate includes a metal substrate or a copper-clad ceramic substrate, etc. The metal substrate is a copper substrate or a molybdenum substrate, etc.
[0021] The thermal expansion coefficient of the interface layer of the composite nanosilver paper after hot pressing is <16×10 -6 K -1 (50~200℃), elastic modulus>50GPa, interface bonding strength is about 30~60MPa.
[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of the composite nano silver paper of the present invention comprises the following steps: mixing a mother solution containing nano ceramic material and silver nanowires and pressing the mixture into the composite nano silver paper; the addition of the nano ceramic material can effectively reduce the thermal expansion coefficient of the sintered body after hot pressing, thereby improving the thermal shock resistance.
[0023] (2) The application of the composite nano silver paper of the present invention has better temperature resistance and performance stability during service due to the addition of ceramic phase in the nano silver paper.
[0024] (3) The application of the composite nano silver paper of the present invention can work under higher temperature, higher voltage, higher current, stronger radiation, higher frequency and higher power conditions due to the addition of ceramic phase in the nano silver paper. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the microscopic morphology of the composite nano-silver paper in Example 1.
[0026] Figure 2 This is the EDS image of the composite nanosilver paper in Example 1.
[0027] Figure 3 This is the microscopic morphology of the composite nano-silver paper in Example 2.
[0028] Figure 4 This is the EDS image of the composite nanosilver paper in Example 2. DETAILED DESCRIPTION
[0029] The present invention will be described in further detail below. Unless otherwise specified, the instruments or materials used in the present invention are commercially available.
[0030] Example 1 The method for preparing a composite nano silver paper with a low thermal expansion coefficient of the present embodiment comprises the following steps: S1. Surface modification of nano-scale high thermal conductivity ceramic material: 0.1 g of 30 nm SiC particles, 100 ml of ethylene glycol, 0.01 g of polyvinyl pyrrolidone, and 0.005 g of sodium laurate sulfate were sealed in a beaker, and placed in a 50° C. water bath for 20 min to obtain a modified nano-scale high thermal conductivity ceramic material; SiC particles are high thermal conductivity ceramic materials, ethylene glycol is a diluent, polyvinyl pyrrolidone is a dispersant, sodium lauryl sulfate is a surfactant, and the modified materials are all water-soluble substances, which can be removed in the subsequent mixing process with the silver nanowire mother solution.
[0031] S2. diluting the modified nanoscale high thermal conductivity ceramic material: pouring the modified nanoscale high thermal conductivity ceramic material into 10L of 40°C deionized water and stirring at 200rpm for 5min to obtain a diluted solution; S3, mixing the diluent and the silver nanowire mother solution (the preparation method can be referred to CN118143263A, which can also be purchased): adding 2L of silver nanowire mother solution with a wire diameter of 100-150nm to the diluent and stirring at 200rpm for 30min to obtain a mixed solution; the solid content ratio of the nano-scale ceramic material in the diluent to the silver nanowire in the silver nanowire mother solution is 1:100; S4. The mixed liquid is subjected to solid-liquid separation, drying and pressing treatment: solid-liquid separation is performed under the action of positive pressure and negative pressure (the solid-liquid separation method can be referred to CN118143263A), and after demolding, vacuum drying is performed at 50°C for 10 minutes, pre-cut according to the size of the substrate, and pre-pressed at 130°C and 3MPa for 4 minutes to obtain a uniform composite nano silver paper with a low thermal expansion coefficient.
[0032] In this embodiment, the thickness of the composite nanosilver paper is 200 μm and the surface density is 0.6 kg / m 2 , the thickness and density fluctuations are about 3%, and the organic impurity content such as PVP is about 0.75%. Figure 1 , 2 It can be seen that SiC is evenly distributed in the nanosilver paper without obvious agglomeration.
[0033] Composite nano silver paper is used for packaging interconnection between substrate and heat sink. The 60mm×60mm silver-plated copper substrate, 60mm×60mm composite nano silver paper and 65mm×65mm heat sink are stacked and placed in a packaging mold. They are hot pressed for 10 minutes at 250℃ and 15MPa for packaging interconnection. The interface bonding strength is about 50MPa. The thermal expansion coefficient of the sintered composite nano silver paper after packaging is about 15.5×10 -6 K -1 (50~200℃), the elastic modulus of the sintered body is about 52GPa.
[0034] Example 2 The method for preparing a composite nano silver paper with a low thermal expansion coefficient of the present embodiment comprises the following steps: S1. Surface modification of nano-scale high thermal conductivity ceramic material: 0.2 g of 20 nm SiC particles, 150 ml of ethylene glycol, 0.01 g of polyethylene glycol, and 0.01 g of alkyl glucoside were sealed in a beaker, and placed in a 70° C. water bath for 20 min to obtain a modified nano-scale high thermal conductivity ceramic material; SiC particles are high thermal conductivity ceramic materials, ethylene glycol is a diluent, polyethylene glycol is a dispersant, and alkyl glucoside is a surfactant.
[0035] S2. diluting the modified nanoscale high thermal conductivity ceramic material: pouring the modified nanoscale high thermal conductivity ceramic material into 4 L of 60° C. deionized water and stirring at 200 rpm for 5 min to obtain a diluted solution; S3, mixing the dilution liquid and the silver nanowire mother liquor: adding 2L of silver nanowire mother liquor with a wire diameter of 50-90nm to the dilution liquid and stirring at 200rpm for 30min to obtain a mixed liquid; the solid content ratio of the nano-scale ceramic material in the dilution liquid to the silver nanowire in the silver nanowire mother liquor is 2:100; S4. The mixed liquid is subjected to solid-liquid separation, drying and pressing treatment: the solid-liquid is separated under a positive pressure of 0.5 MPa until no liquid drips out, and after demolding, it is blown-dried at 40°C for 3 hours, pre-cut according to the size of the substrate, and pre-pressed at 140°C and 5 MPa for 3 minutes to obtain a uniform composite nano-silver paper with a low thermal expansion coefficient.
[0036] In this embodiment, the thickness of the composite nanosilver paper is 150 μm and the surface density is 0.45 kg / m 2 , the thickness and density fluctuations are about 5%, and the content of organic impurities such as PVP is about 1.3%. Figure 3 and Figure 4 As shown, SiC is evenly distributed in the nanosilver paper without obvious agglomeration.
[0037] In this embodiment, the composite nano silver paper is used for packaging interconnection between the substrate and the heat sink. The 30mm×30mm silver-plated copper substrate, the 30mm×30mm composite nano silver paper and the 30mm×30mm silver-plated copper substrate are stacked and placed in a packaging mold. The packaging interconnection is performed by hot pressing at 200°C and 8MPa for 8min. The interface bonding strength is about 40Mpa. The thermal expansion coefficient of the composite nano silver paper sintered body after packaging is about 14.7×10 -6 K -1 (50~200℃), the elastic modulus of the nanosilver sintered body is about 65GPa. The amount of SiC added in Example 2 is increased by 2 times compared with that in Example 1, and the thermal expansion coefficient continues to decrease after hot pressing packaging; at the same time, the solid-liquid separation process in Example 2 is carried out under the action of positive pressure external force, and the separation efficiency is higher; compared with Example 1, the silver wire diameter in Example 2 is smaller, the sintering activity is higher, and the proportion of the diluent is reduced by 3 / 4, the sintering-aiding phases such as PVP in the silver paper are increased, and the packaging process can be completed at a lower temperature, smaller pressure and shorter time.
[0038] Comparative Example 1 The preparation method of a composite nano silver paper in this comparative example is substantially the same as that in Example 1, except that only the solid content ratio of the nano-ceramic material in the diluent to the silver nanowires in the silver nanowire mother liquor is reduced to 0.1:100, and the other conditions remain unchanged.
[0039] During packaging, the packaging interconnection was carried out under the same hot pressing process conditions as in Example 1 (250°C, 15MPa, 10min), the interface bonding strength was about 65MPa, and the elastic modulus of the sintered body was about 60GPa. However, the thermal expansion coefficient of the composite nanosilver paper sintered body after packaging was about 18.57×10 -6 K -1 (50~200℃), which seriously affects the service stability of the device.
[0040] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the technical content disclosed above without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should fall within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing composite nano silver paper with low thermal expansion coefficient, characterized in that: The following steps are involved: S1, diluting the dispersed solution of the surface-modified nano-ceramic material to obtain a diluted solution; S2, mixing the diluent and the silver nanowire mother liquor evenly to obtain a mixed liquor, wherein the solid content ratio of the nano-scale ceramic material in the diluent to the silver nanowire in the silver nanowire mother liquor is 0.3-5:100; S3, subjecting the mixed liquid to solid-liquid separation, drying, and pre-pressing to obtain composite nano silver paper; In step S1, the surface modification includes the following steps: mixing a diluent, a dispersant, a surfactant, and a nano-ceramic material, and dispersing them uniformly in a water bath environment at 40 to 80° C. to obtain a dispersed solution; In the surface modification step, the mass percentage of diluent: dispersant: surfactant: nano-ceramic material is 100-5000: 0.01-0.5: 0.005-0.2: 1; The nano-scale ceramic material is one or more of SiC, AlN, diamond, Si3N4, Al2O3, and the particle size is 10 to 100 nm.
2. The preparation method according to claim 1, characterized in that: Contains at least one of the following features A to C; A. The diluent is one or more of ethylene glycol, glycerol, n-butanol, methyl amyl alcohol, acetic acid, caproic acid, and deionized water; B. The dispersant is one or more of polyvinyl pyrrolidone, polyvinyl butyral, polyethylene glycol, polyacrylamide, polyvinyl alcohol, and polyacrylic acid; C. The surfactant is one or more of silane coupling agent, sodium lauryl sulfate, sucrose fatty acid ester, alkyl glucoside, titanate, tetramethylammonium hydroxide, ethyl carbamate, hexadecyltrimethylammonium bromide, and ethylenediaminetetraacetic acid.
3. The preparation method according to claim 1, characterized in that: The dilution step is: adding the dispersed solution into deionized water and stirring evenly at a temperature of 25-80° C. to obtain a diluted solution.
4. The preparation method according to claim 1, characterized in that: In step S3, the pre-pressing temperature is 120-150° C., the pressure is 3-5 MPa, and the time is 1-5 min.
5. The preparation method according to claim 1, characterized in that: In step S3, the drying temperature is 35-80°C; When the drying is vacuum drying, the drying time is 5 to 10 minutes; When the drying is by forced air drying, the drying time is 4 to 6 hours.
6. Use of the composite nano silver paper prepared by the preparation method according to any one of claims 1 to 5 in the packaging of power electronic power devices.
7. The use according to claim 6, characterized in that: The application includes packaging interconnection between a chip and a substrate, or packaging interconnection between a substrate and a heat sink, wherein the packaging is hot pressing packaging with a temperature of 180 to 250° C., a pressure of 8 to 20 MPa, and a time of 3 to 10 minutes.
Citation Information
Patent Citations
Composite transparent conductive thin film and preparation method thereof
CN104299681A
Inorganic wire material-organic polymer composite material and preparation method thereof
CN108892811A
Superconductive rare earth nano ceramic material and preparation method thereof
CN114716235A
Lightweight lightning protection composite electromagnetic shielding film and preparation method thereof
CN116987455A
Nano-silver paper as well as preparation method and application thereof
CN118143263A
Cited By
Method for realizing low-temperature and low-voltage connection of skutterudite and metal electrode based on nano-silver paper
CN119973264A